2015
DOI: 10.1016/j.ridd.2015.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Social relationship difficulties in autism and reactive attachment disorder: Improving diagnostic validity through structured assessment

Abstract: Children with RAD and children with ASD may demonstrate similar social relationship difficulties but there appears to be a difference in the social quality of the interactions between the groups. In most cases it was possible to differentiate between children with ASD and children with RAD via structured observation. Nevertheless, for a small proportion of children with ASD, particularly those whose difficulties may be more subtle, our current standardised measures, including structured observation, may not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
80
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(89 citation statements)
references
References 42 publications
8
80
1
Order By: Relevance
“…The presence of developmental delays or co-occurring diagnoses, such as ADHD, in addition to ASD symptoms may add complexity to the diagnostic assessment process. Another important consideration is exposure to trauma and attachment disorder; a history suggestive of these problems should prompt the assessor to consider the overlap in presentation between attachment disorders and ASD and seek out expertise as needed 203204205. Given these complexities, cognitive and language assessments and consideration of comorbid emotional behavioral disorders are recommended for all patients with ASD.…”
Section: Additional Elements Of Asd Assessmentmentioning
confidence: 99%
“…The presence of developmental delays or co-occurring diagnoses, such as ADHD, in addition to ASD symptoms may add complexity to the diagnostic assessment process. Another important consideration is exposure to trauma and attachment disorder; a history suggestive of these problems should prompt the assessor to consider the overlap in presentation between attachment disorders and ASD and seek out expertise as needed 203204205. Given these complexities, cognitive and language assessments and consideration of comorbid emotional behavioral disorders are recommended for all patients with ASD.…”
Section: Additional Elements Of Asd Assessmentmentioning
confidence: 99%
“…In previously institution‐reared children, DSEB was associated not only with inattention/hyperactivity and conduct problems, but also with autism‐like behavior and problems in peer interaction (Rutter et al., ). Clinically, the differentiation between DSED and Autism Spectrum Disorder (ASD) is of interest given that both disorders entail problematic social behaviors (Davidson et al., ). It was shown that while symptoms of DSED and ASD co‐occurred in some children, manifestation of DSEB was independent from symptoms of ASD in children with mild intellectual disability, who were referred for psychiatric evaluation (Giltaij, Sterkenburg, & Schuengel, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is good evidence that the assessment of neurodevelopmental and/or psychiatric disorders, including autism, is very challenging in the context of multiple and overlapping co-morbidities amongst children in care, which can arise from a range of interrelated factors including prenatal influences, early trauma and disrupted attachment (DeJong, 2010). The social difficulties that lie at the core of an autism spectrum diagnosis (American Psychiatric Association, 2013) can be misclassified in some cases where there is a history of attachment problems and related behavioural and cognitive difficulties (Davidson et al, 2015). Although differential and co-occuring diagnoses between reactive attachment disorder and/or disinhibited social engagement (for example) and autism is possible Autism spectrum diagnoses of looked-after children 101 (Mayes et al, 2016), there is also acknowledgement that sometimes the subtle nature of differences is very difficult to detect with current assessment measures (Davidson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The social difficulties that lie at the core of an autism spectrum diagnosis (American Psychiatric Association, 2013) can be misclassified in some cases where there is a history of attachment problems and related behavioural and cognitive difficulties (Davidson et al, 2015). Although differential and co-occuring diagnoses between reactive attachment disorder and/or disinhibited social engagement (for example) and autism is possible Autism spectrum diagnoses of looked-after children 101 (Mayes et al, 2016), there is also acknowledgement that sometimes the subtle nature of differences is very difficult to detect with current assessment measures (Davidson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%